SOSIALISASI KESIAPSIAGAAN HADAPI RABIES DI LINGKUNGAN SMP NEGERI 6 KUPANG - Pandarangga, Putri; Wuhan, Yustinus Oswin Primajuni; Saputra, Agus; Amalo, Maria Elizabeth; Dangur, Fransiska Aping; Adeventino, Raul; Repi, Ermelinda Ue; Hoban, Michaelis Conchita Fatima; Prakameng, Dandy (Jurnal Media Tropika, 2025)
Rabies is a zoonotic disease caused by Lyssavirus with a case fatality rate reaching 100%. Lack of public understanding is the main factor in the transmission of rabies to humans. The purpose of this activity is to increase students' preparedness at SMPN 6 Kupang to prevent and treat rabies through educational outreach. The educational approach includes outreach, poster distribution, and educational songs about rabies. Evaluation was carried out using a pre-test and post-test. The outreach activities showed an increase in students' understanding of the definition of rabies, namely from 57.1% to 90.4%; symptoms of rabies in animals from 90% to 93.8%, animals that transmit rabies from 71.9% to 89%, and various other aspects of rabies prevention and treatment. Based on the comparison of pre-test and post-test results, there was an increase in knowledge about rabies, but the difference was not significant. This demonstrates the success of efforts by various parties to communicate about the dangers of rabies to the children of SMPN 6. However, an educational approach through structured, interactive socialization remains effective in increasing the school community's preparedness to face the threat of rabies.